Trophic and reproductive ecology of Hemibrycon sierraensis (Characiformes: Characidae), endemic fish of Gaira River, Sierra Nevada of Santa Marta, Colombia - Ibarra-Trujillo, Eduardo J.; García-Alzate, Carlos A. (Revista de Biología Tropical, 2017)
The study of feeding habits in fishes can give important information about their role in the fish community, their functional role in the ecosystem, and their relationships with all available resources. We studied H. sierraensis from Gaira River and performed eight bi-monthly samples between May 2014 and November 2015. We analyzed fish stomach contents by the numerical (% N), volume (% V) and frequency of occurrence (% FO) methods; we also calculated the index of food importance (IA), coefficient of emptiness (CV), trophic niche breadth (used H ') and condition factor (K). Additionally, we determined the sex ratio, gonadosomatic index (RGS), fecundity, minimum and average size at sexual maturity, and oocyte diameter by standard methods. The Gaira River has irregular meanders with clear waters, and high current velocity through its drainage; it is generally oligotrophic, with a tendency to eutrophic condition in some places. Observed dissolved oxygen values were high (5.4 mg/L), electrical conductivity was 68.63 µS/cm, and pH was found neutral. We analyzed stomach contents of 477 specimens, and found a 1.59 % coefficient of vacuity. The species was found euryphagic in its feeding habits (H'= 0.69), omnivorous tending to insectivorous; its diet consisted mainly of Trichoptera larvae (Atanatolica sp.), followed in importance by snails (Gastropoda Pomacea sp.) and dipteran larvae such as Simulium sp. Significant differences in both frequency of occurrence and the volume consumed were observed for the different size classes, as well as between different seasons of the year. The condition factor indicated that the species was well fed. Sex was determined for 424 fish, of which 241 were male and 181 female, given a ratio of 1.3: 1 (male-female) which resulted significantly different (Chi 2: 16.14; P= 0.02). The gonadosomatic index indicated that reproduction occurs during the high water river phase, fecundity was high, and oocyte diameter was relatively small. Males reached sexual maturity at an average size of 67.08 mm SL, and females at 70.68 mm SL. Their life history strategy is seasonal r. Management and conservation plans for this species are required due to human intervention in their habitat, originated by the growing tourist activity in the area.